Higher Hepcidin Levels in Adolescents with Obesity Are Associated with Metabolic Syndrome Dyslipidemia and Visceral Fat - Reyna Rodríguez-Mortera; Russell Caccavello; Ricardo Hermo; María Eugenia Garay-Sevilla; Alejandro Gugliucci (Antioxidants, 2021)
Tightly regulated iron metabolism prevents oxidative stress. Hepcidin is a hormone that regulates iron flow in plasma; its production is induced by an iron overload and by inflammation. It inhibits iron entry into the circulation by blocking dietary absorption in the duodenum, the release of recycled iron from macrophages and the exit of stored iron from hepatocytes. Varied signals responding to iron stores, erythropoietic activity and host defense converge to regulate hepcidin production and thereby affect iron homeostasis. Although it is known that hepcidin increases when interleukin 6 (IL-6) increases, the relationship between hepcidin, dyslipidemia, insulin resistance (IR) and visceral adiposity index (VAI) in adolescents with obesity is unclear. In this cross-sectional study of 29 obese adolescents and 30 control subjects, we explored the difference of hepcidin, iron metabolism markers and IL-6 between obese and non-obese adolescents, and identified associations with inflammation, atherogenic dyslipidemia and IR. As compared to lean controls, obese participants showed 67% higher hepcidin: 14,070.8 ± 7213.5 vs. 8419.1 ± 4826.1 pg/mLc; 70% higher ferritin: 94.4 ± 82.4 vs. 55.1 ± 39.6 pg/mLa and 120% higher IL-6: 2.0 (1.1–4.9) vs. 0.9 (0.5–1.3) pg/mLd. Transferrin, soluble transferrin receptor and total body iron (as measured by sTFR/ferritin, log10 sTFR/ferritin ratio and sTFR/log ferritin ratios) were not different between the two cohorts. In the whole cohort, hepcidin correlated with VAI (r = 0.29a), sd-LDL (r = 0.31b), HOMA-IR (r = 0.29a) and IL-6 (r = 0.35c). In obese adolescents hepcidin correlated with TG (r = 0.47b), VLDL-C (r = 0.43b) and smaller LDL2 (r = 0.39a). Hepcidin elevation in adolescents with obesity is linked more to inflammation and metabolic alterations than to iron metabolism since the other markers of iron metabolism were not different between groups, except for ferritin. Studies addressing the long-term effects of higher hepcidin levels and their impact on subclinical anemia and iron status are warranted. a p < 0.05; b p < 0.01, c p < 0.001 dp < 0.0001.